Caracterização da matéria orgânica dissolvida nas águas das bacias hidrográficas do estado de Sergipe - Costa, Adnivia Santos (2011)
In this work, the water obtained from six watersheds in Sergipe State from Brazil was analyzed using fluorescence spectroscopy, dissolved organic carbon(DOC) and UVVis absorbance, to characterize the dissolved organic matter (DOM). The water sample were collected in the period from may 2009to january 2010. Twenty-three sampling sites distributed in different rivers from watersheds were used for collection. As results, DOC concentrations showed the following variation: from 0.35 to 34.7mg.L-1 in Sergipe river basin; 0.50 to 18.95mg.L-1 in Piauí river basin;0.93 to 56mg.L-1 in São Francisco river basin; 1.1 to 14.85mg.L-1 in Vaza Barris river basin; 1.7 to 11.85mg.L-1 in Japaratuba river Basin and 20.3 to 27.2mg.L-1 in Real River basin. The synchronous fluorescence spectra presented four peaks (I, II, III and IV) with varying intensities, depending on the localization and period sampling. The highest fluorescence intensity occurred in peaks II and III, showing that the origin of DOM is predominantly terrestrial from a lixiviated soil due to superficial runoff in raining period that occurs from may/09 to september/09. From December/09 to January/10, the peaks I and II were predominant due to autochthonous organic matter produced by algal activity and anthropogenic sources, respectively. In Japaratuba, São Francisco, Piauí and Real basins, was observed a linear regression between DOC and absorbance at 254nm, suggesting that the DOM, in these rivers, are predominantly from land source, consisting of humic substances. Though, in Sergipe and Vaza Barris Basins the nonlinearity of the DOC according to the absorbance at 254nm highlights a significative contribution from anthropogenic sources in the DOM of these rivers. The principal component analysis was applied to data from May(rainy season) and December(dry season) of 2009 and separated the samples from the rainy season into three groups while a single cluster was obtained for the dry season. The most important factor to separate the samples was the qualitative characteristics of DOM in the water. The input of organic matter from terrestrial and anthropogenic origin, transported to rivers by rain water was essential for the separation process.